2021
DOI: 10.3390/biotech10030018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ethyl Methane Sulphonate Mutagenesis in Artemisia vulgaris L. under NaCl Stress

Abstract: The present investigation aimed to obtain salt-tolerant Artemisia vulgaris L. to develop a constant form through in vitro mutagenesis with ethyl methane sulphonate (EMS) as the chemical mutagen. NaCl tolerance was evaluated by the ability of the callus to maintain its growth under different concentrations, ranges from (0 mM to 500 mM). However, NaCl salinity concentration at (500 mM) did not show any development of callus, slight shrinking, and brown discoloration taking place over a week. Thus, all the bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…in EMS-treated plants compared to the control (Anbarasan Brassica rapa was obtained following EMS mutagenesis (Mizuno et al, 2014). The EMS mutated an unknown locus located on chromosome IV in sugar beet beside the bolting gene B loca-photosynthetic pigments (chlorophyll and carotenoid) was observed in EMS-treated callus of Artemisia vulgaris (Kumar and Kumari, 2021). Possible improvement of the photosynthetic activity may have led to higher carbohydrate accumuplants in this study.…”
Section: Discussionmentioning
confidence: 64%
“…in EMS-treated plants compared to the control (Anbarasan Brassica rapa was obtained following EMS mutagenesis (Mizuno et al, 2014). The EMS mutated an unknown locus located on chromosome IV in sugar beet beside the bolting gene B loca-photosynthetic pigments (chlorophyll and carotenoid) was observed in EMS-treated callus of Artemisia vulgaris (Kumar and Kumari, 2021). Possible improvement of the photosynthetic activity may have led to higher carbohydrate accumuplants in this study.…”
Section: Discussionmentioning
confidence: 64%
“…[13] reported that soaking black soybean seeds in EMS increased seed weight. [14] reported that EMS treatment of A. vulgaris callus produced artemisia mutants that were more tolerant to NaCl than controls. EMS treatment also caused flower color changes in T. Patula [15].…”
Section: Figure 2 the Growth Performance Of 5-month-old Artemisia Mut...mentioning
confidence: 99%